Bringing together social-ecological system and territoire concepts to explore nature-society dynamics - Barreteau, Olivier; Giband, D.; Schoon, M.; Cerceau, J.; DeClerck, Fabrice A.J.; Ghiotti, S.; James, T.; Masterson, V.; Mathevet, R.; Rode, S.; Ricci, F.; Therville, C. (Resilience Alliance, Inc., 2016)
We examine two academic traditions that address the nature-society interface. These traditions are organized around two main concepts: social-ecological system and territoire. These traditions have grown independently and are rooted respectively in ecology and social geography. We show that they have much in common: Both come with a systemic view of the nature-society interface and have the intention of understanding better the relations between nature and society and improving their sustainability. However, they differ in how they deal with space and society. We foresee that the combination of both traditions could improve the understanding of these systems, their definition, and their evolution, and hence, the capacity to assess and manage their resilience.